Anxiolytic-like effects of sinapic acid in mice - Yoon, Byung Hoon; Jung, Ji Wook; Lee, Jong-Ju; Cho, Young-Wuk; Jang, Choon-Gon; Jin, Changbae; Oh, Tae Hwan; Ryu, Jong Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Sinapic acid is a phenylpropanoid compound and is found in various herbal materials and high-bran cereals. With the exception of its antioxidant activities, the pharmacological properties of sinapic acid have been rarely reported. The purpose of this study was to characterize the putative anxiolytic-like properties of sinapic acid using an elevated plus-maze (EPM) and hole-board test. Control mice were orally treated with an equal volume of vehicle (10% Tween 80 solution), and positive control mice were treated with diazepam (1 mg/kg, i.p.). Sinapic acid (4 mg/kg, p.o.) significantly increased the percentages of time spent in the open arms of the EPM test (P<0.05). In the hole-board test, sinapic acid also significantly increased the number of head-dips at 4 mg/kg (P<0.05). In addition, the anxiolytic-like properties of sinapic acid examined in the EPM test were blocked by flumazenil or bicuculline, which are GABAA antagonists. Moreover, sinapic acid markedly potentiated GABA current in single cortical neurons in a dose-dependant manner, and reactive I-GABA increased to 1.8 times at 1 mu M of sinapic acid. These results suggested that sinapic acid is a prominent anxiolytic agent, and that its anxiolytic-like effects are mediated via GABAA receptors and potentiating Cl- currents. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: MU-OPIOID AGONIST; PROTEIN-KINASE-C; PHENOLIC-ACIDS; FERULIC ACID; ANTIOXIDANT; PEROXYNITRITE; ACTIVATION; EXTRACTS; GROWTH; L.